2011
DOI: 10.1186/1471-2229-11-172
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging and analysis of differences in cadmium dynamics in rice cultivars (Oryza sativa) using positron-emitting107Cd tracer

Abstract: BackgroundRice is a major source of dietary intake of cadmium (Cd) for populations that consume rice as a staple food. Understanding how Cd is transported into grains through the whole plant body is necessary for reducing rice Cd concentrations to the lowest levels possible, to reduce the associated health risks. In this study, we have visualized and quantitatively analysed the real-time Cd dynamics from roots to grains in typical rice cultivars that differed in grain Cd concentrations. We used positron-emitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 33 publications
3
52
0
Order By: Relevance
“…2b). A similar phenomenon was observed in previous studies of Cd uptake dynamics in rice (Fujimaki et al 2010;Ishikawa et al 2011). This may be explained in terms of the complicated combination of both apoplastic binding and symplastic uptake of Cd by the roots.…”
Section: Uptake By Rootssupporting
confidence: 71%
See 3 more Smart Citations
“…2b). A similar phenomenon was observed in previous studies of Cd uptake dynamics in rice (Fujimaki et al 2010;Ishikawa et al 2011). This may be explained in terms of the complicated combination of both apoplastic binding and symplastic uptake of Cd by the roots.…”
Section: Uptake By Rootssupporting
confidence: 71%
“…This is the first reported study to visualise Cd movement non-invasively in an intact Cd hyperaccumulator, S. plumbizincicola, using 107 Cd tracer and improved PETIS which enabled direct and simultaneous observation of the radiotracer-treated culture solution and plants (Fujimaki et al 2010;Ishikawa et al 2011). The imaging data were applied for quantitative analysis of the dynamics and kinetics of Cd uptake and transport in the whole plant supplied with two different inorganic N sources, NO 3 -and NH 4 + .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratios of radioactivity in the glumes and grains at 4 and 6 h when 65 Zn was fed through the culm cut above the flag-leaf node were about one-fifth those found at 3 and 4.5 h when 109 Cd was fed (Table 4), which indicated that more selective transport to the grains might occur in 65 Zn transport. All the nodes, especially the flagleaf nodes, accumulated intensively radioactive Cd when 107 Cd was administered to the root-bathing medium (Ishikawa et al 2011). The nodes may be the sites of xylem-to-phloem transport leading the radioactive Cd to the panicles.…”
mentioning
confidence: 99%